2010
DOI: 10.1017/s1041610210001481
|View full text |Cite
|
Sign up to set email alerts
|

A short-form version of the Boston Naming Test for language screening in dementia in a bilingual rural community in Galicia (Spain)

Abstract: BNTOu11 is a useful and time-saving method as part of a battery for screening for dementia in a psychogeriatric outpatient unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
2
4
0
4
Order By: Relevance
“…The results have shown that individuals with dementia scored lower than those without dementia on the CLNT and BNT. This finding is consistent with the symptoms of anomia frequently found in the patients with dementia using the BNT (Bayles, Tomoeda, & Trosset, 1992;Lin et al, 2014;Salmon & Bondi, 2009), as well as with the results found in other studies using diverse naming tests (Brouillette et al, 2011;Goldman et al, 2001;Nebreda et al, 2010;Vigliecca, Aleman, & Jaime, 2007). With regard to the possible influence of age and education on the naming tests, we observed that, despite the low education of the control group, their score on the naming tests is similar to the score of the SMC group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results have shown that individuals with dementia scored lower than those without dementia on the CLNT and BNT. This finding is consistent with the symptoms of anomia frequently found in the patients with dementia using the BNT (Bayles, Tomoeda, & Trosset, 1992;Lin et al, 2014;Salmon & Bondi, 2009), as well as with the results found in other studies using diverse naming tests (Brouillette et al, 2011;Goldman et al, 2001;Nebreda et al, 2010;Vigliecca, Aleman, & Jaime, 2007). With regard to the possible influence of age and education on the naming tests, we observed that, despite the low education of the control group, their score on the naming tests is similar to the score of the SMC group.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that different items that compose the test are interrelated to a large extent and measure the same construct. This internal consistency was similar or superior to that of other naming tests obtained in similar studies to ours, such as .912 for the BNT (Nebreda et al, 2010), between .923 and .933 for the TNT, .898 for the Modified Boston Naming TestSpanish, and .776 for the naming subtest of the CERAD Battery (Marquez de la Plata et al, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Durante los últimos años han surgido diferentes versiones reducidas del BNT con el fin de minimizar el tiempo de aplicación de la prueba [32]. Estas versiones del BNT difieren tanto en el modo en que se han obtenido como en el número de ítems que plantean [31][32][33][34][35][36][37][38] (Tabla I). Así, algunas versiones optan por preservar la esencia de la prueba original, manteniendo un criterio de frecuencia léxica y dificultad de los ítems [31,33], mientras que otras adoptan un criterio clínico para identificar los dibujos que mejor discriminan entre mayores sanos y personas con enfermedad de Alzheimer [34], o entre sujetos con y sin alteraciones en la denominación, independientemente del diagnóstico [32].…”
Section: Introductionunclassified
“…El elevado poder discriminativo exhibido por este método se restringe a la muestra utilizada, por lo que la generalización al resto de la población se encuentra sesgada [40]. Un procedimiento alternativo para reducir el número de láminas consiste en aplicar los supuestos de la teoría de respuesta al ítem, de forma que se seleccionen aquellos ítems que forman una prueba homogénea y que mejor discriminan las dificultades en denominación [32,37].…”
Section: Introductionunclassified
“…In response to this lack, they developed tests and software to be used by SLP/Ts during therapeutic sessions. These tests and programs include health-related qualities of life instrument (HRQOL) (Lucas-Carrasco et al, 2011), Boston Naming Test (Nebreda et al, 2011), Parkinson Neuropsychometric Demential Assessment (PANDA) (Gasser et al, 2011), Screen for Caregiver Burden (SCB) (Guerra-Silla et al, 2011), etc. Of course, these tests and programs helped diagnose most linguistic disorders of dementia patients like phoneme building (phoneme migration, substitution and omission errors) in SD patients ( Jefferies et al, 2012).…”
Section: Introductionmentioning
confidence: 99%